Individual-level and community-level factors associated with the family planning use among pastoralist community of Ethiopia: a community-based cross-sectional study - Mussie Alemayehu; Araya Abrha Medhanyie; Elizabeth Reed; Afework Mulugeta (BMJ Open)
Objective The study aimed to identify the effects of the individual-level and community-level factors on the use of family planning (FP) among married women in the pastoralist community of Ethiopia.Design A community-based cross-sectional study was conducted in September 2018. Data were analysed using R software. To determine the fixed effect of individual-level and community-level factors of FP use, a two-level mixed-effects logistic regression was used. The result was described using the Adjusted OR (AOR), and the variance partition coefficient.Setting and participants Afar, Ethiopia (2018; n=891) married women of reproductive age (15–49) years.Primary outcome measures FP use or non-use.Results The current use of FP was 18.7% (16.31%–21.43%). Women who need to walk 1 hour and more to the nearest health facility (AOR 0.14, 95% CI 0.05 to 0.3), have ANC visit of 4 and above (AOR 6.02, 95% CI 1.74 to 20.8), had their last birth at a health facility (AOR 2.71 95% CI 1.27 to 5.81), have five and more children (AOR 4.71, 95% CI 1.86 to 11.9), have high knowledge on FP (AOR 2.74, 95% CI 1.11 to 6.74) and had high intentions to use FP (AOR 10.3, 95% CI 3.85 to 27.6) were more likely to report FP use. The magnitude of the effect of for FP use was smaller than that of 9 of the 13 individual factors. Apart from this 19.4% of the total variance in the odds of using FP attributed to between community difference (intraclass correlation coefficient=0.194). Regarding the community-level characteristics, clusters of having higher electronic media possession (AOR 2.84, 95% CI 1.2 to 6.72) and higher women decision making on FP (AOR 8.35, 95% CI 2.7 to 27.1) were significantly associated with increased FP use compared with clusters with lower reports of these aspects.Conclusion FP use among the pastoralist community is influenced by both individual cluster/community-level characteristics or factors. Even though the effect of clustering in FP use was large in comparison with the unexplained between-cluster variation, it was lower than the individual-level factors.Trail registrtion number NCT03450564